Effects of Management Culture and Pedagogic Competence on Teacher Performance with Work Motivation: A Case Study of Vocational School Teachers in Ternate City - Prince Charles Heston Runtunuwu (Jurnal Mantik, 2020)
Teachers are professional educators who have the main task of teaching, guiding, directing, training, assessing and evaluating students. There is another phenomenon which reveals that low work motivation for some teachers causes a decrease in teacher teaching performance. The purpose of this study was to examine and analyze: 1) the influence of organizational culture and pedagogical competence on teacher performance and motivation, 2) the influence of organizational culture and pedagogic competence through work motivation on teacher performance.This study uses a quantitative approach, to analyze the causality of the influence of independent variables on the dependent variable. This research was conducted at Public and Private Vocational High Schools (SMK) in Ternate City and was carried out in 2019. The population in this study were teachers in Public and Private Vocational High Schools (SMK) in Ternate City. The total population is 353 people. The type of data used in this study is primary data sourced from respondents through a questionnaire distribution. While secondary data was obtained from the 2015 UKG results summary and the 2015-2017 National Examination result documentation. Validity and reliability tests used thecorrelation coefficient product moment andcriteria Cronbach's Alpha and Item-to-Total Colerations using the computer assistance of the SPSS (Statistical Package for Social Science) program.